Research and development of 3D printed vasculature constructs. (30th April 2018) - Li, Xinda; Liu, Libiao; Zhang, Xinzhi; Xu, Tao
Abstract: Artificial blood vessels must be strong, flexible, and must not lead to blockage after implantation. It is therefore important to select an appropriate fabrication process for products to meet these requirements. This review discusses the current methods for making artificial blood vessels, focusing on fabrication principle, materials, and applications. Among these methods, 3D printing is very promising since it has the unique capability to make complicated three-dimensional structures with multiple types of materials, and can be completely digitalized. Therefore, new developments in 3D printing of artificial blood vessels are also summarized here. This review provides a reference for the fusion of multiple processes and further improvement of artificial blood vessel fabrication.